Pengaruh Kemampuan Motorik, Imagery dan Motivasi Terhadap Hasil Belajar Lay-up Shoot - Gilang Ramadan; Destiana Ayu Ningrum (JUARA : Jurnal Olahraga, 2019)
The purpose of this study was to determine whether there is a direct or indirect influence between motor skills, imagery, and motivation on the learning outcomes of the layup shoot. Testing the hypothesis of the influence of motor skills on shoot lay-up learning outcomes of 0.659. The effect of imagery on the shoot lay-up learning outcomes is 0.621. The effect of motivation on the shoot lay-up learning outcomes is 0.764. The effect of motor skills on motivation is 0.625. The effect of imagery on motivation is 0.782. The effect of motor skills on shoot lay-up learning outcomes through motivation is 0.915. The effect of imagery on shoot lay-up learning outcomes through motivation is 0.960. There is a positive influence between motor skills on the learning outcomes of the lay-up shoot. There is a positive influence between imagery on the learning outcomes of the lay-up shoot. There is a positive influence between motivation on learning outcomes of lay-up shoot. There is a positive influence between motor skills and motivation. There is a positive influence between imagery on motivation. There is a positive influence between motor skills on the learning outcomes of shoot lay-up through motivation. There is a positive influence between imagery on learning outcomes of lay-up shoots through motivation.